1994
DOI: 10.1111/j.1600-0773.1994.tb00330.x
|View full text |Cite
|
Sign up to set email alerts
|

Cardiotoxicity of Doxorubicin: Effects of Drugs Inhibiting the Release of Vasoactive Substances

Abstract: The therapeutic usefulness of doxorubicin, an antineoplastic drug, is limited by its cardiotoxicity whose mechanism is as yet unknown. Several hypotheses have been postulated including also the release of vasoactive substances, so the aim of the present investigations was to study the relationship between the release of vasoactive substances and the development of doxorubicin-induced cardiotoxicity. The effects of the following drugs on doxorubicin-induced (cumulative dose of 20 mg/kg intraperitoneally) cardio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
22
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(25 citation statements)
references
References 27 publications
3
22
0
Order By: Relevance
“…The ethanol extract demonstrated increase in the body weight gain along with the gain in weight of heart and the heart/body weight ratio. Doxorubicin treatment causes prolongation of P wave, QRS complex, QT interval and RR interval while reduces cardiac cycle (Rossi et al, 1994;Danesi et al, 1986). Results of this study showed that, in comparison to the group treated with doxorubicin alone, rats pretreated with extract have nearly normal ECG data and significantly prevented ST segment prolongation throughout the study period.…”
Section: Discussionmentioning
confidence: 55%
“…The ethanol extract demonstrated increase in the body weight gain along with the gain in weight of heart and the heart/body weight ratio. Doxorubicin treatment causes prolongation of P wave, QRS complex, QT interval and RR interval while reduces cardiac cycle (Rossi et al, 1994;Danesi et al, 1986). Results of this study showed that, in comparison to the group treated with doxorubicin alone, rats pretreated with extract have nearly normal ECG data and significantly prevented ST segment prolongation throughout the study period.…”
Section: Discussionmentioning
confidence: 55%
“…At this point, contractile function has not yet significantly declined in the isolated perfused hearts ex vivo under basal conditions but calcium handling was already impaired (as evidenced by increased intracellular end-diastolic calcium concentration), indicative of early-stage myocardial calcium overload. While this early-stage increase in myocardial intracellular calcium does not necessarily or immediately impair contractile function, it has been shown to contribute to the late-stage morphological and functional alterations associated with doxorubicin cardiomyopathy [21,23]. Furthermore, the estimated Ca i 2+ sensitivity of the contractile machinery is significantly decreased in the doxorubicin-treated hearts.…”
Section: Discussionmentioning
confidence: 87%
“…It is well established that doxorubicin induces profound disturbances in myocardial calcium handling [8,21,23]. The focus of the current study was to investigate whether the PARP pathway regulates the alterations in calcium handling provoked by doxorubicin treatment.…”
Section: Discussionmentioning
confidence: 99%
“…DOX-induced cardiac damage does not only affect mechanical functions of the heart, but also results in inhomogeneity of ventricular depolarization and repolarization reflected by the occurrence of changes in the ECG [27]. The most consistent ECG changes following DOX-induced cardiotoxicity include widening of QRS, QT interval prolongation, and T-wave flattening [28]. The significance of the Sα-T segment is another parameter, which has been considered in the evaluation of cardiotoxicity induced by DOX in rodents [29].…”
Section: Discussionmentioning
confidence: 99%